Health awareness and youth: A study on the impact of visual and caption in the cigarette packets on youth - Ramdas, Deepthi; Balasubramanian, Arumugam (Elsevier Ltd., 2014)
In recent times smoking has been considered as a synonym of youth.The Government of India has taken initiative to create awareness about the health consequences of smoking.The image on the cigarette packets to gorier and disturbing pictures is an example for the same.In this paper the researchers analyzed the impact of the warning caption and image on the cigarette packets on the youth.Based on survey method and focus group discussion it was found that the warning captions and visuals are not communicating the message in an appropriate way.